PEMBERDAYAAN UMKM GETHUK PISANG MELALUI INOVASI KEMASAN DAN PEMASARAN DIGITAL SEBAGAI PRODUK UNGGULAN DESA PANDANSARI, KECAMATAN PURWOASRI, KABUPATEN KEDIRI - Prima Ayu Rizqi Mahanani; Adellia Putri Maulana; Aqeila Na’imatul Haya; Elvianabila Aprilia; Dwi Asmarani; Rahmatul Luqyana; Aatka Rosane Dewi Kasari; Wahyu Ratna Anjani; Binti Nurlela; Clarissa Azarine Febryana (Marsialapari: Jurnal Pengabdian Kepada Masyarakat, 2025)
Micro, Small, and Medium Enterprises (MSME) play an important role in boosting the village economy, including in Pandansari Village, Purwoasri District, Kediri Regency. One of the important local strengths is processed banana getuk. However, the main challenges faced by local MSMEs are unattractive product packaging and limited access to conventional marketing channels. This study aims to improve the capacity of banana getuk MSMEs by implementing innovations in packaging and digital marketing strategies so that this product can become a mainstay in Pandansari Village. The results of this study show that the packaging is more attractive, environmentally friendly, and in line with modern marketing standards. In addition, the use of social media and digital platforms has expanded market reach and increased sales. This research has proven effective in strengthening the competitiveness of local MSMEs and promoting sustainable village economic growth.